Corpus cavernosum from men with vasculogenic impotence is partially resistant to adenosine relaxation due to endothelial A(2B) receptor dysfunction - Faria, M. (2011)
ABSTRACT Although adenosine has been implicated in penile erection in human males, the receptor subtype responsible for adenosine regulation of human corpus cavernosum (HCC) smooth muscle tone is still a matter of debate. Using selective adenosine agonists and antagonists, we aimed at characterizing the adenosine receptors mediating relaxation of precontracted (with 1 M phenylephrine) HCC strips. HCC specimens were collected from control subjects (organ donors) and from patients with severe vasculogenic erectile dysfunction (ED). In control subjects, adenosine and 5 -N-ethyl-carboxamide adenosine (NECA) fully relaxed HCC. The selective A2A receptor agonist 2-[4-(2-p-carboxy ethyl)phenylamino]-5 -N-ethylcarboxamido adenosine (CGS21680C) produced only a partial relaxation (30–50%) of HCC, which could be further enhanced by simultaneous application of 100 M NECA. The selective A2B receptor antagonist N-(4-acetylphenyl)-2-[4-(2,3,6,7-tetrahydro- 2,6-dioxo-1,3-dipropyl-1H-purin-8-il)phenoxy] acetamida (MRS1706) (10 nM) attenuated NECA-induced relaxation without affecting CGS21680C action. The A2A receptor antagonist 4-{2-[7-amino-2-(2-furyl)[1,2,4]triazolo-[2,3-a][1,3,5]triazin-5- ylamino]ethyl}phenol (ZM241385) (50 nM) consistently reduced the actions of both agonists. In contrast to CGS21680C, NECAinduced relaxation was attenuated when endothelial production of NO and prostanoids was reduced by 100 M NG-nitro-Larginine and 10 M indomethacin, respectively. HCC strips from patients with vasculogenic ED were partially resistant to NECA but kept relaxation to CGS21680C; the remaining effect was sensitive to blockade of A2A receptors with 50 nM ZM241385. Data suggest that adenosine regulates HCC smooth muscle tone through the activation of two receptor populations, CGS21680C-sensitive (A2A) and -insensitive (A2B) receptors, located on smooth muscle fibers and on endothelial cells, respectively. Endothelial dysfunction may be correlated with a loss of adenosine A2B receptor activity in penile vessels from men with vasculogenic ED.